Pātī phvaiʹ caññʻʺ puṃ ʼa khre khaṃ caññʻʺ myanʻʺ lupʻ thuṃʺ lupʻ naññʻʺ myāʺ (Mranʻ māʹ Chuirhayʻlacʻ Lamʻʺ cañʻ Pātī, 1971)
Procedures of the constitutional rules of the Burma Socialist Programme Party.